Pengaruh Akuntabilitas Pengelolaan Keuangan Desa, Trans-paransi, dan Kebijakan Desa Terhadap Kesejahteraan Masyarakat - Kurnia Kurnia; Sultan Sultan; Rifqa Ayu Dasila (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study examines the effects of accountability in village financial management, transparency, and village policy on community welfare. Using a quantitative approach and multiple linear regression analysis of 53 respondents in Ponrang Sub-district, Luwu Regency, the results show that accountability has a negative effect, while transparency and village policy have a significant positive effect on community welfare. Village policy is identified as the most dominant variable. These findings reinforce public sector governance theory, highlighting the important role of transparency and policy quality in improving community welfare. This study emphasizes the importance of balancing control and flexibility in village financial management.